China’s Images in Self-Media Videos after the Implementation of China’s Visa-Free Policy: The First 2 Years - Gan, Tianyi; Liu, Lingling (Journal of Theory and Practice in Humanities and Social Sciences, 2025)
After the implementation of China’s Visa-Free Policy in 2023, China’s tourism industry has ushered in a new era of prosperity. At the same time, as social media continues to rise in popularity, many facets of China, including its cuisine and traditional culture, have been widely shared, prompting more and more international travelers to opt for China as their destination. This article studies 20 Self-Media Videos about travel to China following the announcement of China's Visa-Free Transit Policy, which were posted by self-media bloggers from ten various nations or regions. Based on the Positive Discourse Analysis theoretical framework, in light of Appraisal System Theory, by examining the keywords including high-frequency nouns, affective adjectives and verbs, this article seeks to investigate China’s image through corpus analysis. This research indicates that after the implementation of the visa-free policy, more and more foreign tourists have come to China. They have discovered that China has acquired new images including cuisine, mobile payment and so on, and in their eyes, China's image is positive and favorable.